School Curriculum (KSP) Fast Track: Integration of Google Tools and Artificial Intelligence in KSP Development - Kamila Harahap (Asian Journal of Management Analytics, 2026)
This study addresses the challenge of creating an authentic and adaptive school curriculum (KSP) in Indonesia, where administrative burden often leads to generic "copy-paste" documents. The core challenge is the complex, time-consuming KSP development (4-6 weeks) and the lack of intensive teacher support. This paper introduces the KSP Fast Track innovation, integrating Google Tools and Artificial Intelligence (AI) to transform the supervisory process. The methodology involved using Google Classroom as a Digital Command Center, Gemini AI for automatic KSP analysis/recommendations based on educational report data, and Google Meet for real-time, substantive coaching. Results show a significant 70% reduction in KSP development time (down to 1-2 weeks) and the successful creation of authentic, adaptive KSP documents. This transforms the supervisor's role into an inspirational coach, focusing on educational quality rather than administrative checks.